A methodology for the identification of physical parameters of soil-foundation-bridge pier systems from identified state-space models. (15th March 2022) - Carbonari, Sandro; Dezi, Francesca; Arezzo, Davide; Gara, Fabrizio
Highlights: Direct identification of physical parameters of soil-foundation-pier systems from tests. Identification of numerical model parameters without calibration strategies. The method allows the experimental identification of the soil-foundation compliance. The method provides a tool for the identification and localisation of damage in bridges. The identification of damage at the foundation level can be obtained. Abstract: A methodology for the identification of the physical parameters of a model describing the transverse dynamics of soil-foundation-pier systems founded on piles is presented in this paper, starting from identified state-space models of the systems obtained from results of dynamic experimental tests and identification techniques available in the literature. By assuming the order of the model to be compliant with that of a numerical one suitably developed to capture the dynamics of the bridge pier, the procedure allows the identification of the stiffness, mass and damping matrices of the analytical model from which the physical parameters of the real system (e.g. masses, pier stiffness matrix and soil-foundation impedance) can be extracted by directly comparing the components of the identified and analytical matrices. The procedure allows the direct definition of the numerical model that best fits the experimental data without the need of any model calibration, and permits the identification of the soil-foundation compliance taking into account its intrinsic frequency-dependent behaviour. Firstly, the dynamics of the analytical model is formulated adopting the continuous-time first-order state-space form. The model includes the frequency-dependent behaviour of the soil-foundation system through the introduction of a lumped parameter model able to reproduce the typical soil-foundation impedances of pile foundations. Then, an identification strategy of the physical parameters of a generic realistic soil-foundation-pier system is proposed starting from the discrete-time state-space model identified from dynamic tests. The procedure is illustrated with some applications, simulating results of forced vibration and ambient vibration tests executed on a known system whose parameters are then identified according to the proposed approach. The procedure revealed to be effective to identify the stiffness, mass and damping matrixes of the known system, and consequently its physical parameters.